A RCT of non-surgical treatment for intermittent claudication in femoro-popliteal disease: 12-month results - Mazari, Fayyaz Ali Khan; Mehta, Tapan; Abdul Rahman, Mohd Norhisham Azmi; McCollum, Peter Thomas; Chetter, Ian Clifford (Wiley, 2009)
Objective To compare percutaneous transluminal angioplasty (PTA), a supervised exercise programme (SEP) and combined therapy (PTA + SEP) in the treatment of intermittent claudication (IC) due to femoro‐popliteal disease.